2019
DOI: 10.1007/s00432-019-03056-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of treatment outcomes in localised and metastatic spermatocytic tumors of the testis

Abstract: Introduction Because spermatocytic tumors of the testis are rare, only limited evidence exists regarding the malignant potential and the optimal management of localized and metastatic disease. Materials and methods We performed a systematic review through MEDLINE, EMBASE, Scopus, Cochrane Database of Systematic Reviews and Web of Science to identify reports including patients with testicular spermatocytic tumors. Results From originally 7863 studies, we extracted data of 146 patients of which 99% were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…It has been suggested that the size of human spermatocytic tumor is correlated to the incidence of metastasis. It is reported that the average size of metastatic spermatocytic tumor was 92.5 mm, while 67.5 mm in non-metastatic spermatocytic tumor, indicating that the metastatic spermatocytic tumor is statistically signifi cantly larger than the nonmetastatic one [7]. Considering that it was a small dog weighing 3.32 kg, the size of the tumor was remarkably large (8 8 10 cm 3 ) in this case.…”
Section: Embryonal Cell Carcinomamentioning
confidence: 60%
See 1 more Smart Citation
“…It has been suggested that the size of human spermatocytic tumor is correlated to the incidence of metastasis. It is reported that the average size of metastatic spermatocytic tumor was 92.5 mm, while 67.5 mm in non-metastatic spermatocytic tumor, indicating that the metastatic spermatocytic tumor is statistically signifi cantly larger than the nonmetastatic one [7]. Considering that it was a small dog weighing 3.32 kg, the size of the tumor was remarkably large (8 8 10 cm 3 ) in this case.…”
Section: Embryonal Cell Carcinomamentioning
confidence: 60%
“…It is previously reported that the origin of the metastasized tumor is a sarcomatous component in human spermatocytic tumors [3]. Thus, it has been suggested that sarcomatous transformation is one of the predictors of metastasis in spermatocytic tumors [7]. Here, however, we report a canine metastatic spermatocytic tumor, which is an extremely rare case even without any sarcomatous and anaplastic changes.…”
Section: Introductionmentioning
confidence: 59%
“…The theory that spermatocytic tumor precursor cells originate in embryogenesis is disputed[ 3 ]. Some scholars[ 1 ] believe that spermatocytic tumor develops from mature cells such as pachytene spermatocytes. A recent study found that these tumor cells express reproductive cell-specific markers[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatocytic tumor is a rare malignancy that accounts for 0.61% of testicular germ cell tumors[ 1 ]. Tumor development is independent of ethnicity and a history of cryptorchidism.…”
Section: Introductionmentioning
confidence: 99%
“…Very limited data are available in the adjuvant setting in this patient population (26) where feasibility has been reported also in patients over 70. A single course of adjuvant chemotherapy, either carboplatin for seminoma or BEP for non-seminoma, can be proposed in well informed patients, also considering the much more aggressive treatment (and maybe not feasible) that would be required in case of recurrence.…”
Section: Treatments and Related Toxicitiesmentioning
confidence: 99%